The role of legitimacy in pursuing environmentally responsible transportation practices. (15th December 2016) - Ellram, Lisa M.; Golicic, Susan L.
Abstract: Shippers and carriers have been slow to pursue reduced freight transportation emissions, despite progress made in reducing emissions elsewhere in the supply chain. The purpose of this research is to specifically explore the legitimacy-related motivations for utilizing a voluntary environmental partnership (VEP) to improve environmentally responsible freight transportation practices (ERTP). This research develops propositions through case studies of U.S. shippers and carriers in an effort to better understand motivations for and perceived benefits from pursuing these practices through joining or not joining the SmartWay transportation VEP. The findings indicate that pragmatic and moral legitimacy are the primary legitimacy drivers of joining a VEP and implementing these practices. The benefits associated with membership in a transportation VEP are viewed positively overall, though more so by shippers than by carriers. Whether the company joined the VEP entirely of its own volition, as in the case of most shippers studied, or under perceived pressure from a customer impacts the perceived outcomes of VEP membership. The findings further suggest that membership in a transportation VEP can help reduce greenhouse gas emissions and reduce costs, which could encourage and expand these practices toward a cleaner environment. Highlights: A case study of transport companies was conducted to examine emissions practices. Voluntary environmental partnership (VEP) membership may support emissions reduction. Carriers join a transport VEP primarily for pragmatic legitimacy reasons. Shippers join a transport VEP for moral legitimacy or mixed reasons. Voluntarily joining a VEP is associated with a positive view of VEP outcomes.